Crystal structure of (E)-4-(4-ethylbenzylidene)-6,8-dimethoxy-3,4-dihydrobenzo[b]oxepin-5(2H)-one, C21H22O4 - Zhu, Wen-Xin; Xia, De-Li; Miao, Yu-Hao; Pan, Yu-Xin; Meng, Qing-Guo; Hou, Gui-Ge (Zeitschrift für Kristallographie. New crystal structures, 2025)
, orthorhombic, (no. 61), = 9.1326(5) Å, = 14.0165(9) Å, = 26.9851(19) Å, = 3454.3(4) Å , = 8, ) = 0.0433 (2685), ) = 0.0965, T = 293 K.